2018
DOI: 10.1530/eje-17-0991
|View full text |Cite
|
Sign up to set email alerts
|

Do aggressive variants of papillary thyroid carcinoma have worse clinical outcome than classic papillary thyroid carcinoma?

Abstract: When other clinicopathological factors were similar, patients with TCV did not exhibit unfavorable clinical outcome, whereas those with CCV had significantly poorer clinical outcome. Individualized therapeutic approach might be necessary for each type of AV-PTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
(51 reference statements)
1
52
0
Order By: Relevance
“…2b) and a poor prognosis. [113][114][115][116] It is a rare subtype of PTC accounting for only 0.15-0.2% of all PTC 115 ( Table 2). As typical PTC-type nuclear features are not seen in columnar cell variant PTC, 117 it was excluded from the PTC lineage and classified in other tumors in the Japanese classification of thyroid tumors proposed by the Guidelines for Clinical Practice for the Management of Thyroid Nodules in Japan 2015.…”
Section: Columnar Cell Variant Ptcmentioning
confidence: 99%
“…2b) and a poor prognosis. [113][114][115][116] It is a rare subtype of PTC accounting for only 0.15-0.2% of all PTC 115 ( Table 2). As typical PTC-type nuclear features are not seen in columnar cell variant PTC, 117 it was excluded from the PTC lineage and classified in other tumors in the Japanese classification of thyroid tumors proposed by the Guidelines for Clinical Practice for the Management of Thyroid Nodules in Japan 2015.…”
Section: Columnar Cell Variant Ptcmentioning
confidence: 99%
“…Recently, a retrospective study compared DFS in 144 patients with three aggressive variants of PTC and 763 patients with classic PTC, after propensity score matching by age, sex, primary tumour size, LN metastasis and ETE. This study found that the group of aggressive PTC variants had significantly lower DFS than the matched classic PTC group (HR = 2.16 (95% CI 1.12-4.16), P = 0.018) (Song et al 2018). However, when TCVs and CCVs were evaluated separately, there was no significant differences in DFS and dynamic risk stratification (DRS) between patients with TCV (n = 121) and matched classic PTC, whereas the CCV group (n = 18) had significantly poorer DFS than the matched classic PTC group (HR = 12.19 (95% CI 2.11-70.33), P = 0.005) (Song et al 2018).…”
Section: Histological Variantsmentioning
confidence: 65%
“…However, when TCVs and CCVs were evaluated separately, there was no significant differences in DFS and dynamic risk stratification (DRS) between patients with TCV (n = 121) and matched classic PTC, whereas the CCV group (n = 18) had significantly poorer DFS than the matched classic PTC group (HR = 12.19 (95% CI 2.11-70.33), P = 0.005) (Song et al 2018). Furthermore, CCV was an independent risk factor for structural recurrence in multivariate analysis (HR = 4.28 (95% CI 1.66-11.00) P = 0.001), suggesting the use of individualised therapeutic approaches for each type of aggressive PTC variant (Song et al 2018).…”
Section: Histological Variantsmentioning
confidence: 95%
“…The mutation rate of BRAF gene,localed in V600E, was high in CCV-PTC, about 33% [2].There were 3 cases of CCV-PTC found BRAF mutation out of 9 cases, 2 cases with clinical invasive. IHC showed that, the expression of cyclin D1 and Ki -67, in the nucleus, were higher, which P53 weakly positive in in invasive and inert CCV -PTC.…”
Section: Geneticsmentioning
confidence: 89%
“…Papillary thyroid carcinoma is the most common thyroid cancer, about 60%-70%, and often encountered in children and adolescents, especially young women [1][2][3]. Age has a significant impact on prognosis, which is good in young patients and poor in old patients.…”
Section: Introductionmentioning
confidence: 99%